Transient mutism and cerebellar ischemic stroke - Luis Rafael Moscote-Salazar; Hernando Alvis-Miranda; Angel Lee; Hector Farid Escorcia; Sandra Milena Castellar-Leones (Romanian Neurosurgery, 2013)
The ischemic stroke is one of the most common conditions in our hospitals, representing 50% of revenues of neurology services. A variety of processes is cerebral ischemic myocardial cerebellum. Cerebellar infarction is not a rare disease, representing between 2 to 4% of all cerebrovascular events in clinical and autopsy series, and their ratio is 4-5 times higher than cerebellar hemorrhage. Although it is increasingly documented, it rarely Recognized stills like a phenomenon. Mutism occurs primarily in children and occasionally in adults as a well-recognized complication of posterior fossa surgery. Rarely been reported transient mutism associated with cerebellar infarction as isolated episode.